DOP72 The association of anti-tumor necrosis factor and thiopurine therapy with the risk of lymphoma among Inflammatory Bowel Disease patients: A nation-wide study from the epi-IIRN. (21st January 2022) - Waterman, M; Lavi, I; Harel, S; Focht, G; Loewenberg Weisband, J; Greenfeld, S; Kariv, R; Ledderman, N; Matz, E; Keinan-Boker, L; Eizenstein, S; Dotan, I; et al.
Abstract: Background: To clarify the risk of lymphoma in patients with inflammatory bowel diseases (IBD) exposed to anti-tumor necrosis factor (anti-TNF) and/or thiopurines we aimed to evaluate the Israeli IBD population. Methods: A nested case-control study on the epidemiology cohort of the Israeli IBD Research Nucleus (epi-IIRN) including all 4 Health Maintenance Organizations in Israel linked to the Israeli Cancer Registry. Patients diagnosed since 1.1.2005 until 31.12.2015 (42, 954 patients) were included and followed until 31.12.2017. Each lymphoma case was matched to 30 non-lymphoma IBD patients by age, gender, IBD subtype, and date of earliest evidence of IBD in the database. Patients with other risk factors for lymphoma, or lymphoma diagnosis prior to IBD diagnosis were excluded (figure 1). Conditional logistic regression was used to compute the association of drug exposure (anti-TNF, thiopurines and combination) with diagnosis of lymphoma. Patients without exposure to anti-TNF and/or thiopurines in each group served as reference within each group. Additionally, sub-group analyses by gender, age group at inclusion (≤48, 49–64, ≥65), time from last drug exposure (≤90 days, 91–365 days, >365 days) were done. Results: The final nested cohort included 5556 IBD patients (185 lymphoma cases matched to 5, 371 without lymphoma). Mean follow-up (F/U): 5.5±3.5 years, 50% with Crohn's disease, mean age at database entry 52.6±17.80 years. Anti-TNF-only exposure was documented in 4.3% (8/185) of lymphoma cases vs. 2.6% (145/5, 371) of controls OR 1.97, CI 0.93–4.16, p=0.07; in males the ORs were 2.84 (CI 1.17–6.92 p=0.04) and increased to OR 3.48 (CI 1.55–7.88, p=0.002) for males <48 years and OR 2.87 (CI 1.53–5.37, p=0.001) for patients with last exposure ≤90 days (figure 2). Exposure to combination anti-TNF+thiopurines occurred in 8.6% (16/185) of lymphoma cases vs. 5.3% (282/5, 371) of controls OR 2.09 (CI 1.17–3.73, p=0.013). Males on anti-TNF-thiopurine combination had OR of 3.42 (CI 1.37–8.52, p=0.003) and in sequential (non-overlapping exposure to both thiopurines and anti-TNFs during F/U) combination an OR of 2.74 (CI 1.02–7.35 p=0.02). Thiopurine-only exposure occurred in 15.1% (28/185) of lymphoma cases vs. 13.5% (726/5, 371) of controls, OR 1.32 (CI 0.86–2.03, p=0.20). Males on thiopurines had an OR of 1.75 (CI 1.02–2.99, p=0.05). The risk increased further in males <48 years OR 2.17 (CI 1.01–4.66, p=0.047) and in males aged≥65 OR 3.50 (CI 1.55–7.82, p=0.002). Females were not at risk for lymphoma (figure 3). Conclusion: This nationwide study suggests that exposure to anti-TNF therapy alone or in combination with thiopurines may be associated with an increased risk of lymphoma, but only in males, especially when last exposure occurred within 90 days.